1977
DOI: 10.1113/jphysiol.1977.sp011970
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prolonged inactivity upon the contraction characteristics of fast and slow mammalian twitch muscle (cat)

Abstract: SUMMARY1. Prolonged inactivity of soleus (slow twitch) and medial head of flexor digitorum longus (fast twitch: previously commonly known as flexor hallucis longus and hereafter referred to as FDL) muscles of the cat was produced by sodium pentobarbitone anaesthesia or spinal isolation. Isometric contraction characteristics were examined after 4-22 days and 8-49 days respectively.2. Sleep of up to 3 weeks' duration was associated with progressive changes in the weight, maximum tetanic tension, speed of contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
9
2
1
Order By: Relevance
“…As a result of denervation, adult cat slow and fast hind limb muscles show reduced speed of contraction (Syrovy et al 1972;Kean et al 1974). Prolonged inactivity induced the same changes in cat muscles (Davis & Montgomery 1977). Immobilization did not lead to any significant changes in the speed o€ contraction in hind limb muscles of the guinea pig (Maier et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of denervation, adult cat slow and fast hind limb muscles show reduced speed of contraction (Syrovy et al 1972;Kean et al 1974). Prolonged inactivity induced the same changes in cat muscles (Davis & Montgomery 1977). Immobilization did not lead to any significant changes in the speed o€ contraction in hind limb muscles of the guinea pig (Maier et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The force decreased disproportionately more than the wet weight of the disused muscle (Eccles, 1941;Fischbach and Robbins, 1969;Davis and Montgomery, 1977). The slight to moderate diminution in force, present on day 8, disappeared gradually, probably because of a gradual increase in cross-sectional area of the muscle fibres.…”
Section: Electrical Activity At a Fixed Force Of 5 Kgmentioning
confidence: 91%
“…Accordingly, marked atrophy of type 1 fibers in the quadriceps, after knee injury or immobilization by plaster casts, have been shown during the first month, and atrophy of both types after 2–6 months of immobilization [14, 15]. Experimental studies in cats and rats showed that the strength decreased disproportionately more than the weight in a disused muscle [16, 17]. A combination of T/A analysis and MFCV could contribute to the assessment in the study of the weakness of a disused muscle.…”
Section: Discussionmentioning
confidence: 99%